Development of Medium and Bioreactor System for the Cultivation of Hairy Roots of Datura Metel and Scopolamine Production - Law, Sen Yu (2004)
The effects of phytohormones (auxin and cytokinin), sucrose and the ratios of ammonium to nitrate upon root branching and elongation of Datura metel hairy roots were studied on modified B5O medium. Addition of phytohormones in the medium is fatal to Datura metel hairy root cultures. However, root branching and root elongation were enhanced with addition of nitrate at a concentration of 9mM-36mM without any ammonium in the medium.